The Role of Professional Ethics, Independence, and Work Experience in Auditor Performance - Marisca, Prita; Septiano, Renil; Aryadi, Didi; Dona, Elva; Heryanto, Heryanto (AIBPM Publisher, 2024)
This study aims to analyze the influence of professional ethics, independence, and work experience on auditor performance at Regional Office 2 of PT Bank Negara Indonesia (Persero) Tbk in West Sumatra, Riau, and Riau Islands. This research is quantitative research with the intention to test models that reveal the relationship between research constructs, namely professional ethics, independence, work experience and auditor performance. Interviews and questionnaires distributed to bank auditors using complete sampling approaches were utilized to gather data for this study. The analysis method used is multiple linear regression. The results showed that (1) Professional ethics have a positive and significant influence on auditor performance, (2) Independence has a positive and significant influence on auditor performance, (3) Work experience has a positive and significant influence on auditor performance, (4) Professional ethics, independence, and work experience together have a significant influence on auditor performance. The implication of this study is the importance of maintaining professional ethics, independence, and improving auditors' work experience to improve the quality of performance in conducting audits.